A pregação pela arte:um estudo da obra de Confaloni como via pulchritudinis - Pinto, Ana Kelly Ferreira Souto (2024)
The thesis "Preaching through Art: A Study of Confaloni's Work as Via Pulchritudinis" investigates the importance of art in Christian evangelization, focusing on the works of Frei Nazareno Confaloni, a Dominican friar and modernist artist. Centered on the frescoes located in the São Judas Tadeu Parish in Goiânia, the study aims to understand how art, through the concept of Via Pulchritudinis (the Way of Beauty), can serve as a powerful instrument for preaching and spiritual elevation for the faithful. The research is structured into four chapters, covering everything from the definition of preaching within Christianity and the Dominican tradition to a detailed analysis of Confaloni's life and work, as well as the reception of his works by the local community. The first chapter explores the concept of preaching in Christianity, highlighting the fundamental role that the Word of God has always played in spreading the faith. It examines the transition from the initial forms of preaching, such as those practiced by the apostles, to the conception of preaching in the Dominican tradition, to which Frei Confaloni belonged. In this context, the Via Pulchritudinis is presented as a method of evangelization that uses beauty as a means of spiritual ascent, following the Augustinian philosophy that links beauty with truth and goodness. The thesis discusses how this approach has been revitalized in recent papal documents, which encourage artists to use their skills to elevate the human spirit and promote the faith. In the second chapter, Confaloni's life and work are contextualized, detailing his education, influences, and contributions to modern art in Goiás. The artist friar, born in Italy, brought with him a deep influence of modernism, which he applied to his religious art. His work is highlighted as an intersection between sacred art and modernism, reflecting a synthesis between tradition and innovation. This chapter also discusses Confaloni's social role, as he significantly contributed to the democratization of access to art in Goiânia through his art and teaching, leaving a lasting legacy. The third chapter focuses on the aesthetic and phenomenological analysis of the three main frescoes located in the São Judas Tadeu Parish. This analysis seeks to understand how the pictorial images are interpreted by the faithful and how they contribute to the meditation and spirituality of the churchgoers. Art is viewed not merely as a decorative element but as an active component in preaching and catechesis, helping the faithful to reflect on the mysteries of the Christian faith. Phenomenology is used to investigate the artist's intentions and the multiple meanings that his works may carry, considering both the liturgical context and the architectural space where the frescoes are placed. In the fourth chapter, the results of a field study conducted among the attendees of the São Judas Tadeu Parish are discussed. Through questionnaires, the research sought to understand how the community perceives and interprets Frei Nazareno's frescoes and whether these works fulfill the goal of spiritually uplifting and catechizing the faithful. The results indicate that, although the frescoes are widely appreciated for their beauty, there is a lack of aesthetic education among the faithful, which may limit a deeper understanding of the Christian message conveyed through the art. The thesis concludes that for the Via Pulchritudinis to be fully effective, there must be an ongoing effort to educate and raise awareness about the importance of beauty in religious experience. Finally, the thesis reaffirms the relevance of sacred art as a means of preaching in the contemporary era, arguing that Confaloni's work, with its blend of modernism and spirituality, continues to be a powerful example of how art can be used to convey the Christian message and inspire deep meditation on the values of faith. This research contributes to the field of Religious Studies by offering a new perspective on the interaction between art, spirituality, and evangelization, highlighting the importance of educating the faithful for a fuller appreciation of sacred art in its religious contexts. This research was supported by a PROSUC scholarship from the Coordination for the Improvement of Higher Education Personnel (CAPES)